Niveles de plagio y uso de normas para presentación de trabajos en un programa de pregrado en la ciudad de Barranquilla. - Nieto Mendoza, Isaac (Revista Pensamiento Americano)
Introduction: A research study was conducted related to the accepted undergraduate work to opt for the academic degree at the university studied in the city of Barranquilla, Colombia between 2015 and 2020. Objective, Method and/or methodology: This research aimed to characterize the academic production of a program in the city of Barranquilla, emphasizing aspects such as the modality of degree, research methodology, use of standards for submission of papers established by the American Psychological Association (APA) by means of a quantitative methodological design and descriptive-documentary type. Results and conclusions: Of the 50 theses evaluated, 64% were monographs, 86% of the works were not presented under APA standards and 44% presented plagiarism levels between 10 and 15%. These results show the lack of rigour in the review of the degree projects, in violation of the criteria established in the grade work regulations of the studied program in terms of their structure, levels of plagiarism and use of APA standards.